2010
DOI: 10.1021/ja104134e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonds between Nitrogen Donors and the Semiquinone in the QB Site of Bacterial Reaction Centers

Abstract: Photosynthetic reaction centers from Rhodobacter sphaeroides have identical ubiquinone-10 molecules functioning as primary (QA) and secondary (QB) electron acceptors. X-band 2D pulsed EPR spectroscopy, called HYSCORE, was applied to study the interaction of the QB site semiquinone with nitrogens from the local protein environment in natural and 15N uniformly labeled reactions centers. 14N and 15N HYSCORE spectra of the QB semiquinone show the interaction with two nitrogens carrying transferred unpaired spin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…Owing to the influence of the nuclear quadrupole interaction, no corresponding peak is detected near n I ( 14 N) in the 14 NH YSCORE spectrum shown in Figure2A. [16,17,19,43] To directly identify the origin of these signals, we constructed histidine and lysine auxotrophsf rom the E. coli JCB4023 strain. Inner membrane vesicles containing overproduced NarGHI werep urified and titrated to generate MSK D in equilibrium conditions.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the influence of the nuclear quadrupole interaction, no corresponding peak is detected near n I ( 14 N) in the 14 NH YSCORE spectrum shown in Figure2A. [16,17,19,43] To directly identify the origin of these signals, we constructed histidine and lysine auxotrophsf rom the E. coli JCB4023 strain. Inner membrane vesicles containing overproduced NarGHI werep urified and titrated to generate MSK D in equilibrium conditions.…”
Section: 1mentioning
confidence: 99%
“…Assigning the detected 1 Ha nd 14 Nn ucleit oaparticular chemical group is not straightforward. For this purpose, various strategies have been used, including (i)uniform enrichment of the protein in 2 H [12][13][14] or 15 N [15][16][17][18][19][20][21][22] or of the solvent thankst oH 2 O/ 2 H 2 Oe xchange experiments; [12,[23][24][25][26][27][28] (ii)theoretical calculations of hyperfine and quadrupolar parameters, [13,[29][30][31][32][33] (iii)reconstitution experimentsu sing exogenous quinones with various substituents or chemically labeled with 2 H, [29,34] and (iv) comparison with spectroscopic data obtained on model SQs measured in organic solvents. [35][36][37][38][39] Ad irect and more physiological strategy relies on in vivo isotope labeling of individual amino acids or sets of amino acids,w hich,h owever,r equires engineered auxotrophics trains supplemented with isotopically enriched amino acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…He was not only brilliant and open in his thinking, but was a ''hands on'' person, and did experiments with us, turning and adjusting knobs, and sometimes even swearing. We collaborated on three topics, publishing four research papers: (1) With my PhD student Paul Jursinic, Colin and I showed, in 1978, a detailed and important relationship of membrane potential with microsecond delayed fluorescence from plants and algae, a topic he had earlier contributed to with Tony Crofts (see Jursinic et al 1978); (2) With several of our PhD students, Colin andI showed, in 1989 and1992, that bicarbonate, which my Lab had shown to be essential in the reduction and protonation of mobile quinone molecules in plants, algae and cyanobacteria (Shevela et al 2012), was not needed at all in a similar reaction in anoxygenic photosynthetic bacteria (Shopes et al 1989;Wang et al 1992); (3) With Vladimir Shinkarev, Colin's long-time brilliant associate, Colin and I succeeded, in 1997, in obtaining new information on the kinetics of oxygen evolution via chlorophyll a fluorescence measurements .…”
Section: On My Friend Colinmentioning
confidence: 99%
“…Early work identified the two-electron gate of Q B (Wraight 1977), and demonstrated once and for all that protonation was associated with electron transfer to this species (Wraight 1979a, b). This work continued throughout his career, probing the redox potential dependence of protonation (Maroti andWraight 1988a, b, 1997), crucial amino acids in the binding domain (Takahashi and Wraight 1990, Shinkarev et al 1993, Rinyu et al 2004, Martin et al 2010, Maroti et al 2015a and the effect of replacing the native ubiquinone with a variety of others (McComb et al 1990.…”
mentioning
confidence: 99%